A conjugation polyimine vitrimer: Fabrication and performance. Issue 22 (9th November 2018) - Zheng, Hua; Liu, Qi; Lei, Xingfeng; Chen, Yanhui; Zhang, Baoliang; Zhang, Qiuyu
ABSTRACT: Although polyimine vitrimers are a promising and invaluable class of self‐healing materials owing to their great maneuverability and fast exchange of crosslinks without catalysts, it remains a challenge to improve the mechanical properties and thermal stability of the material by simply designing their internal structures. Herein, we report a conjugation polyimine vitrimer, which was prepared by polycondensation of terephthaldehyde, m‐xylylene diamine and tris (2‐aminoethyl) amine as crosslinker. The incorporation of m‐xylylene diamine endows the materials with an expanded conjugation structure, which greatly improves its mechanical properties and thermal stabilities. On the other hand, m‐xylylene diamine is less toxic and irritant than the linear aliphatic ones usually used, which makes the reactions more environment‐friendly. Results show that these materials have excellent mechanical properties and thermal stability, perform good flexibilities after immersed in water and show very short relaxation times at elevated temperatures. In addition, especially, they exhibit good self‐healing efficiency under the condition of heat, water and amine solvents without the need for any catalyst. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 2531–2538 Abstract : Thermoset polymers with excellent thermal stability, mechanical properties, and self‐healing efficiency were obtained for conjugation structure and dynamic imine linkages.